Environmental Assessment for Radioactivity of Radon and Radium In Serum Blood Samples in Bladder Cancer Patients - Al-Sadi, Mohamed Abdul Kadhim Hadi; Ahmed Samir Naje (International Journal of Computational and Experimental Science and Engineering, 2025)
In this work, the CR-39 track detector was used to measure the levels of radon and radium in human blood samples for two groups, firstly healthy (control) and secondly bladder cancer patients. A total of fifty-six blood samples were obtained from Babylon Governorate, Iraq. The concentrations of radon and radium in the control group, which consisted of healthy adults, ranged from (62.121-233.333) Bq.m-3 and (1.207 - 4.533) Bq/kg respectively, according to our results. When comparing the blood samples between the two groups, we found a significant increase in the levels of radon and radium in the group of patients with bladder cancer as a result of their exposure to radioactive contamination, as the range of radon and radium concentrations in their blood serum samples ranged from (116.667-421.717) Bq.m-3 and (2.267-8.193) Bq/kg respectively. Smoking did not show any effect on increasing the levels of radon and radium in the study samples of the infected group, as the average concentrations were close in smokers and non-smokers, While smoking habit showed a clear effect on the blood samples of healthy individuals, as the results showed that the concentrations of radon and radium gas in smokers were higher than in non-smokers. Radon and radium concentrations were found to be significantly higher in the 50-64 age group in the patient group, while radon and radium concentrations were much lower in the healthy group compared to it. The older age group (65-79) recorded a higher concentration than the younger age group (50-64), as the concentration increases with the age of the people due to the occurrence of the accumulation condition, generally, most of the outcomes are above the acceptable international thresholds. There were statistically significant differences in the data obtained (p˂0.05), and a strong positive significant correlation was found between the persons' age group and smoking habit and the concentrations of radon and radium.